Education and Earnings in Arkansas - Harry Anthony Patrinos; Angelica Rivera (Global Labor Organization (GLO), 2025)
This paper presents the first analysis for Arkansas using 2024 CPS data to examine education's impact on earnings and returns to investment. Average returns are 7.7%, higher for women (9%). University education yields even more: 8.8% overall, 8.1% for men, and 10.8% for women. With full discounting, private returns are 11.5% and social returns 6.6%, suggesting social benefits may be undervalued. The key takeaway is that investing in better and broader access to education offers strong individual and societal returns, making it one of the most effective ways to boost economic outcomes.
Keywords: I26; J24; J31; 330; Returns to education; Human capital; Wage differentials; Earnings function; Arkansas